Grid convergence analysis of an H-Darrieus wind turbine for multiple blade configurations - Sanjaya Baroar Sakti Nasution; Dian Morfi Nasution; Elang Pramudya Wijaya; Oki Suprada Ompusunggu (Universitas Negeri Padang, 2026)
Mesh size and number significantly affected the accuracy of CFD simulations in wind turbine analysis. However, most studies focused solely on turbine performance, such as the blade torque or power coefficients. Therefore, this study adopted a broader perspective by analyzing the influence of mesh resolution on both aerodynamic performance and key fluid-dynamic parameters, including vorticity and pressure coefficients, for an H-type Darrieus vertical-axis wind turbine. Two-dimensional CFD simulations were performed using ANSYS Fluent with the k–ω SST turbulence model. Five mesh levels were evaluated across different blade configurations, and the Grid Convergence Index (GCI) was used to quantify discretization errors. The results indicate that increasing mesh resolution yields more stable torque predictions and improved resolution of near-wall flow features, with consistent grid-convergence behaviour observed across all blade configurations. GCI analysis shows that discretization errors consistently decrease as the mesh becomes finer. It also shows that a grid size of about 1.6 x 105 cells is sufficient to keep errors below 5%. These findings show that including flow-field details in mesh sensitivity analysis gives a better way to check the accuracy of CFD simulations for Darrieus wind turbines.